Diffuse Systemic Sclerosis with Brainstem Encephalitis: A Case Report: An Illustrative case - Puppala, Sumirini; Choudhury, Surjyaprakash S; Acharya, Abhijit; Dash, Shree (International Clinical Neuroscience Journal, 2025)
Brainstem encephalitis (BE) is a rare disease that affects 1 in 10,000 individuals each year. However, quite little is known about the aetiologies causing brainstem encephalitis. Scleroderma is a rare connective tissue disorder with pathophysiology still under research. We hereby report a case of systemic sclerosis that primarily presented with brainstem encephalitis, a relatively uncommon presentation, and was retrogradely evaluated, assessed, and diagnosed as diffuse systemic sclerosis (Ds-SSc). Systemic sclerosis is associated with multisystem involvement (multiple internal organs simultaneously or sequentially) and is associated with increased morbidity and mortality, with uncommon involvement of the brainstem. Hence, in any case of brainstem encephalitis in a young patient with no apparent infectious cause, an elaborate examination of all systems and autoimmune profiles must be performed to enable rapid initiation of treatment and, therefore, improve prognosis.